THE ROLE OF THE SUB DISTRICT GOVERNMENT IN STUNTING PREVENTION AND REDUCTION IN MANTUIL SUB DISTRICT, SOUTH BANJARMASIN DISTRICT, BANJARMASIN CITY - Erna Suryani (Penerbit Lafadz Jaya, 2023)
This study intends to explain the role of urban planning in preventing and reducing stunting in Mantuil Sub District, South Banjarmasin District, Banjarmasin City. In this study, the type of research used is descriptive, while the approach is qualitative. The data is collected using in-depth interviews, observations, and documents. The results of the study obtained show that the role of urban Sub districts in preventing and reducing stunting in Mantuil Sub District has been carried out well; this is shown by the existence of stunting prevention and reduction policies carried out by supporting and collaborating with related agencies and at the same time socializing them. Keeping and participating in supplementary feeding activities universal activities to prevent stunting, with the assistance of the Banjarmasin city government to build sanitation or toilets, the Sub district also intensifies efforts to clean under the house from plastic waste, education to the community to protect the environment together, carry out Sub district stunting workshops and carry out Sub district self-supervision in the context of preventing and reducing the number of stunting sufferers. The obstacles faced by the Sub district government in preventing and reducing stunting rates are still a low level of public education, economic limitations of the community, and the existence of marriage at a young age. Some residents have difficulty getting clean water, and the environment could be better, especially with sanitation problems. There are still residents of Mantuil Sub District who move directly to the river because their houses are above the river, while other residents also still use river water for bathing, washing clothes, and other things, except for drinking water.